Revitalizing Maine’s Service Centers - Melrose, John (Maine Policy Review, 2003)
Maine’s 77 “service center” municipalities account for a large proportion of all the state’s consumer retail sales, jobs, services, and tax revenues from income, sales and property taxes, and are home to most of the state’s higher education and health care institutions. However, John Melrose points out that Maine’s public policy turns “worse than a blind eye” to these communities. He presents the policy recommendations put forth in a strategic plan by the Maine Service Centers Coalition for supporting and strengthening service centers. These include leveling the financial playing field between service centers and other communities; improving local government administration to lower costs; reorganizing the delivery of public services; investing financial, human and social capital; and removing barriers to compact development.
Keywords: Maine; service centers; Maine local government